Analysis of the Zinc Finger Domain of TnpA, a DNA Targeting Protein Encoded by Mobilizable Transposon Tn4555 - Bacic, Melissa K.; Jain, Jinesh C.; Parker, Anita C.; Smith, C. Jeffrey (East Carolina University, 2007)
The mobilizable transposon Tn4555, found in Bacteroides spp., is an important antibiotic resistance element encoding a broad spectrum beta-lactamase. Tn4555 is mobilized by conjugative transposons such as CTn341 which can transfer the transposon to a wide range of bacterial species where it integrates into preferred sites on the host chromosome. Selection of the preferred target sites is mediated by a DNA-binding protein TnpA which has a prominent zinc finger motif at the N-terminus of the protein. In this report the zinc finger motif was disrupted by site directed mutagenesis in which two cysteine residues were changed to serine residues. Elemental analysis indicated that the wildtype protein but not the mutated protein was able to coordinate zinc at a molar ration of 1/1. DNA binding electrophoretic mobility shift assays showed that the ability to bind the target site DNA was not significantly affected by the mutation but there was about a 50% decrease in the ability to bind single stranded DNA. Consistent with these results, electrophoretic mobility shift assays incorporating zinc chelators did not have a significant affect the binding of DNA target. In vivo, the zinc finger mutation completely prevented transposition/integration as measured in a conjugation assay. This was in contrast to results in which a TnpA knockout was still able to insert into host genomes but there was no preferred target site selection. The phenotype of the zinc finger mutation was not effectively rescued by providing wild-type TnpA in trans. Taken together these results indicated that the zinc finger is not required for DNA binding activity of TnpA but that it does have an important role in transposition and it may mediate protein/protein interactions with integrase or other Tn4555 proteins to facilitate insertion into the preferred sites. Originally published Plasmid, Vol. 58, No. 1, July 2007
Keywords: Bacteroides; Transposons; Zinc finger; Site-specificity